2010
DOI: 10.2175/106143009x442899
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Lipid Degradation in an Upflow Anaerobic Sludge Blanket Reactor by Integration with an Acidogenic Reactor

Abstract: This work was conducted to investigate the lipids inhibition and their degradation in dairy wastewater treatment. Two-phase system, composed of an acidogenic continuously stirred tank reactor (CSTR) and an upflow anaerobic sludge blanket (UASB) reactor was compared with a single phase system, conventional UASB reactor. The systems were operated up to organic loading rate of 8.09 g COD/L/d and lipid loading rate of 2.94 g COD/L/d. The twophase systems showed higher COD removal (1.19 times), lipids removal (1.92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Although the advantages of two-stage over single-stage digestion systems are addressed in the literature [119,[124][125][126][127][128], there is a lack of adequate research available in terms of comparison between the performances of single, two, or multi-phase co-digestion systems. Kim et al [129] developed a two-stage system comprised of a continuously stirred tank reactor for acidogenesis and a methanogenic upflow bed reactor for the treatment of a high lipid wastewater from a milk and ice cream factory, co-digested with slaughter house wastewater. They obtained a 1.2-times increase in the COD removal, 1.9-times increase in lipids removal, and 1.4-times increase in the methane production compared to the single phase system.…”
Section: Digester Stagementioning
confidence: 99%
“…Although the advantages of two-stage over single-stage digestion systems are addressed in the literature [119,[124][125][126][127][128], there is a lack of adequate research available in terms of comparison between the performances of single, two, or multi-phase co-digestion systems. Kim et al [129] developed a two-stage system comprised of a continuously stirred tank reactor for acidogenesis and a methanogenic upflow bed reactor for the treatment of a high lipid wastewater from a milk and ice cream factory, co-digested with slaughter house wastewater. They obtained a 1.2-times increase in the COD removal, 1.9-times increase in lipids removal, and 1.4-times increase in the methane production compared to the single phase system.…”
Section: Digester Stagementioning
confidence: 99%
“…Some slaughterhouse wastewater treatment plants (WWTP) have a secondary anaerobic reactor, usually based on upflow anaerobic sludge blanket (UASB) or expanded granular sludge bed (EGSB) reactor systems, due to the high organic content of the intake. Several successful experiments at laboratory, pilot and industrial scale with such wastewater and reactor configurations are reported in the literature (Kim and Shin, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the UASB is the most effective treatment technology for soluble contaminants. A COD reduction of 77%, a BOD reduction of 87%, a TSS reduction of 47.1%, a TDS reduction of 57%, an oil and grease reduction of 92%, and a chloride reduction of 49.8% are the effluent removal rates for UASB from dairy wastewater (Kim and Shin, 2010;Gotmare et al, 2011;Passeggi et al, 2012;Uma, 2012, 2013;Chen et al, 2014;Couras et al, 2015;Elangovan and Sekar, 2015;Banu et al, 2015;Lavanya and Jodhi, 2016;Picos-Benítez et al, 2017;Batubara et al, 2018;Zhuang et al, 2018;Gundkal et al, 2019;Heydari et al, 2019;Jin et al, 2019;Yang et al, 2019;Lim et al, 2020;Mainardis et al, 2020).…”
Section: Methodsmentioning
confidence: 99%